2020
DOI: 10.1186/s13018-020-02016-7
|View full text |Cite
|
Sign up to set email alerts
|

The importance of preoperative T1 slope for determining proper postoperative C2–7 Cobb’s angle in patients undergoing cervical reconstruction

Abstract: Background This study aimed to explore the relationship among different cervical sagittal parameters in asymptomatic volunteers and the correlation between surgical efficacy and difference of presumed and actual postoperative C2–7 Cobbs’s angle (C2–7COBB), which was calculated based on preoperative T1 slope (T1S) in patients undergoing cervical reconstruction. Methods In total, 158 inpatients with cervical spondylosis and 274 asymptomatic volunteers were retrospectively reviewed. Cervical sagittal parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…Cervical lordosis is influenced by thoracic kyphosis; thus, the TIA and T1S have also been introduced to evaluate the stability of the cervical spine. 17 Recent research has suggested that a high T1S is a potential risk factor for the development of MC due to impaired sagittal balance, especially in the C5-C6 cervical segment. 18 Therefore, in this study, we performed further analysis of the preoperative, postoperative and follow-up TIA and T1S.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical lordosis is influenced by thoracic kyphosis; thus, the TIA and T1S have also been introduced to evaluate the stability of the cervical spine. 17 Recent research has suggested that a high T1S is a potential risk factor for the development of MC due to impaired sagittal balance, especially in the C5-C6 cervical segment. 18 Therefore, in this study, we performed further analysis of the preoperative, postoperative and follow-up TIA and T1S.…”
Section: Discussionmentioning
confidence: 99%
“… 11 It's defined in different ways, like local angle, cervical curvature, and cervical relative offset position, and is not easy to grasp in practice. 1 , 3 , 12 , 13 , 14 But distinct age differences have been observed in cervical sagittal alignment, and it is one of the key risk factors influencing the cervical sagittal alignment. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 So, we propose a reconstruction algorithm for cervical sagittal alignment based on age difference.…”
Section: Discussionmentioning
confidence: 99%
“…The aims of surgical treatment are to completely alleviate the compression of dural sac, reconstruct the stability of the cervical spine, and restore the curvature of the cervical spine in accordance with the biomechanical characteristics. 2 , 3 , 4 Decompression and stabilization have been recognized surgical goals, and the techniques are generally well‐established. With the research progresses of sagittal balance, it is taken more and more seriously for cervical sagittal alignment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations